(untitled) (Research, Society and Development, 2022)
Objectives: To assess methodological differences between studies that analyzed the association between gestational diabetes mellitus and prematurity. Methods: The selection of articles was carried out between October 2020 and January 2021 in the PubMed, Virtual Health Library (Lilacs/Bireme/BVS Brasil), Embase and Scopus databases. The following descriptors were used: “Gestational Diabetes Mellitus” and “Prematurity”, which were modified according to the indexing rules of each database. There was no restriction on publication period and language. Twelve studies were selected, being two cross-sectional, five cohorts, four control cases and one clinical trial. Results: Most studies used the National Diabetes Data Group criteria for the diagnosis of gestational diabetes mellitus. Of the selected studies, six observed an association between gestational diabetes mellitus and prematurity. Conclusion: In addition to the impact of the multifactorial causality of prematurity, studies that did not find an association between gestational diabetes mellitus and prematurity showed methodological differences, especially regarding the definition, screening and diagnosis of gestational diabetes mellitus, which may lead to different results.